Is there a EU copyright jurisprudence?: an empirical analysis of the workings of the European Court of Justice - Favale, Marcella; Kretschmer, Martin; Torremans, Paul (Wiley, 2016)
The Court of Justice of the European Union (CJEU) has been suspected of carrying out a harmonising agenda over and beyond the conventional law-interpreting function of the judiciary. In relation to the development of a EU copyright law, the Court has seen a dramatic increase in activity, with 6 cases filed in the 10 years following the Phil Collins case of 1992, 6 cases filed in the 5 years between 2002 and 2006, and 26 cases in the 5 years between 2007 and 2011. This study aims to investigate empirically two theories in relation to the development of EU copyright law: (i) that the Court has failed to develop a coherent copyright jurisprudence (lacking domain expertise, copyright specific reasoning, and predictability); (ii) that the Court has pursued an activist, harmonising agenda (resorting to teleological interpretation of European law rather than – less discretionary – semantic and systematic legal approaches). The findings of the study confirm the former, and qualify the latter.